State of the Art of the Methods for Modelling Data: Architecture of an Information System - Reyna Monteverde, Tino Eduardo (2016)
This paper details the latest research on the subject of this research, “Method of Data Architecture Modelling to ensure robustness and stability”. The structure of the paper is organized in two main blocks:A. Data ModellingB. Methods of Data Modelling These issues are the main elements of the present investigation. Clearly identify the concept and modellingactivity is critical for support the whole development of the method. Data analysis is one of the critical issues, bythe very nature of this stage is not operational but thoughtful. Many times, technical staff often avoids it becauseis tedious, hence the importance of finding a rigorous and practical technique, which possessing sense for thebusiness area. Finally, as all trade information system is directed towards the company, then you should take into account the business patterns to merge with the technological model.